O projeto político do partido dos trabalhadores em Cachoeiro de Itapemirim-ES e a gestão (2009-2012) no âmbito dos pilares do modo petista de governar - Caetano, Joana D'Arck (2014)
This dissertation examines the trajectory of the Partido dos Trabalhadores (Workers Party) in Cachoeiro de Itapemirim, south of the state of Espírito Santo, and ita arrival to power in the 2008 elections, as well as the performance of the PT administration in 2009-2012 considering the political, economic and social mood that was the scenario form the object of study. The survey of the emergence of the city, its natural, economic, political, social and cultural aspects are important for understanding the history of this time factor. The research also examines the emergence and trajectory of PT (Workers Party) in Brazil, Espirito Santo, with emphasis in Cachoeiro de Itapemirim and the coming to power in the city. Come on the agenda for further discussion, the contradictions of PT to participate in the election and move away from its social base. With the coming to power in Itapemirim-ES, a municipality that has many priority needs, noticeably when it comes to urban infrastructure of the suburbs, which grew haphazardly and without the handling of the government, the PT government is faced with the challenge of following the guidelines of the PT way of Government, founded on popular participation, the "inversion of priorities" and ethics and transparency in government. The proposal is to verify that the PT administration during its first term (2009-2012) followed the above parameters and the results of those actions for the population, especially in the periphery areas, which are more dependent on the public social policies.